A Novel Chemical Binding Primer to Improve Dentin Bonding Durability. (July 2022) - Yu, S.Y.; Zhang, J.H.; Li, K.X.; Chen, H.; Wang, H.M.; He, X.; Shi, Z.S.; Zhu, S.; Cui, Z.C.
The dentin collagen matrix that is not completely enveloped by resin adhesive is vulnerable to degradation by intrinsic collagenases during the etch-and-rinse process, which contributes to the deterioration of the bonding interface. Current commercial adhesives have no functional components that can form covalent bonds to the dentin collagen matrix. In this study, a photocurable aldehyde, 4-formylphenyl acrylate (FA), was synthesized and for the first time applied as a primer in adhesive dentistry to covalently bind to collagen. Experimental groups with different concentrations of FA (1%, 3%, 5%, 7%, 9%) were prepared as primers. The cytotoxicity was evaluated by live/dead-cell staining and thiazolyl blue tetrazolium bromide assay. The interaction of FA with collagen was examined by attenuated total reflection Fourier transform infrared spectroscopy, hydroxyproline release under the degradation of type I collagenase, and thermogravimetric analysis. An optimal group was selected based on the degree of conversion of 2 universal adhesives and further divided depending on the treatment time (20 s, 30 s, 1 min, 2 min). The bonding performances were evaluated by microtensile strength before and after aging. Finally, the bonding interface was observed under confocal laser scanning microscopy and scanning electron microscope. The results indicated that FA demonstrated good biocompatibility, dentin modification capability, and infiltration. It not only effectively cross-linked dentin collagen to improve its stability against enzymatic hydrolysis and modify the adhesive interface but also potentially acted as a diluting monomer to induce deep penetration of adhesive resin monomers into the dentin. The bonding strength after aging was improved without jeopardizing the degree of conversion of 2 commercial adhesives. Such prominent advantages of using FA to improve the bonding performance promotes its further application in adhesive dentistry.